Assessment of Water Quality and Presence of Enterobacteria in the Billings-Tamanduateí Watershed and Its Relationship with Social Indicators - Beatriz Guedes-Pereira; Romeu Randefran Souza Dantas; Juliana Mendonça Silva de Jesus; Isabela Gagliardi Ortiz; Gabrielle Segatti Soares Almeida; Rodrigo de Freitas Bueno; Luís César Schiesari; Ricardo Hideo Taniwaki (Limnological Review)
Water quality in urban streams is closely linked to socioeconomic conditions, particularly in densely populated and poorly sanitized areas. This study evaluates the physicochemical and microbiological quality of water in the Billings-Tamanduateí sub-basin and investigates its correlation with social indicators such as population density, informal settlements, and lack of sewage treatment. Water samples were collected from 14 sub-basins, analyzing parameters, including dissolved organic and inorganic carbon, total dissolved nitrogen, pH, dissolved oxygen, oxidation-reduction potential, conductivity, and the presence of enterobacteria (Escherichia coli, Enterococcus, and Pseudomonas aeruginosa). Statistical analyses revealed strong associations between water quality degradation and increased population density, lack of sanitation, and lower per capita income. The findings reinforce that socially vulnerable areas are the most affected, with higher levels of organic and microbiological contamination. Despite improvements in sewage collection over time, gaps in wastewater management persist, even in major metropolitan areas such as São Paulo. Future studies could expand the analysis to include less vulnerable regions for comparison and explore the impacts of climate change on urban stream water quality. The results highlight the urgent need for improved sanitation infrastructure and policies to mitigate contamination and protect public health.